The influence application of Information Technology and Competence on Employee Productivity through Job Satisfaction in the Civil Apparatus at Hasanuddin University - Muhammad Erfan; Mahlia Muis; Andi Ratna Sari Dewi (Magister Management, Hasanuddin University, 2020)
This study aims to analyze (i) the effect of information technology variables on job satisfaction; (ii) the effect of competency variables on job satisfaction; (iii) the effect of information technology variables on work productivity; (iv) the effect of competency variables on work productivity; (v) the effect of job satisfaction variables on work productivity; (vi) the influence of information technology variables on work productivity through job satisfaction variables; and (vii) the effect of competency variables on work productivity through job satisfaction variables. The quantitative approach is used to test and analyze the factors that influence job satisfaction and work productivity. Research location at Hasanuddin University, Makassar City. The population in this study were Unhas employees with the status of ASN (State Civil Apparatus) as many as 935 people. The sampling method uses probability sampling with a simple random sampling technique. Withdrawing the number of samples using the Slovin formula, which produces 90 people as a minimum number. Data collection techniques using a questionnaire with a measurement scale used is a Likert scale with five components. Data analysis techniques in this study used path analysis. The results showed that information technology and competency variables significantly influence job satisfaction and work productivity. Information technology and competence have a significant effect on work productivity through job satisfaction variables. All hypotheses are accepted and supported by previous research.